Free convection boundary layer on a sphere with constant surface heat flux in a micropolar fluid - Nazar, R.; Amin, Norasahaida; Grosan, T.; Pop, I. (Elsevier Science Ltd., 2002)
The present paper considers the steady laminar free convection boundary layer flow over an a sphere with a surface heat flux place in a micropolar fluid. The governing boundary layer equations are first transformed into a non-dimensional and the resulting nonlinear system partial differential equations are then solved numerically using the Keller-box method. Numerical results presented include the local wall temperature distribution and the locak skin friction coefficient for a wide range of martial parameter K. The Prandtl is taken to be 0.7 and 7, respectively